Current Advances in Wearable Devices and Their Sensors in Patients With Depression - Lee, Seunggyu; Kim, Hyewon; Park, Mi Jin; Jeon, Hong Jin (Frontiers in Psychiatry, 2021)
In this study, a literature survey was conducted on the development and use of wearable devices and sensors in the study of depression. We collected 29 studies that used wearable devices for the assessment, monitoring, and treatment of depression. We investigated the sensors of the various types of wearable devices and investigated how the parameters measured through sensors can be used in depression studies. The studies included devices such as wristbands including smartwatches, wearable forehead electroencephalogram, inertial sensors on feet, and light therapy glasses. In addition, we discussed the advantages and disadvantages of wearable devices in the field of depression. The continuous, objective monitoring of symptoms and novel treatments developed through wearable devices will lead to new changes in the diagnosis and treatment of depression. In the process, it will be necessary to solve problems such as limitations in the types of collected data as well as reliability and privacy issues of wearable devices.